Evolution of the Reliability of the Fully Implantable Middle Ear Transducer Over Successive Generations. Issue 4 (April 2015) - Debeaupte, Mathilde; Decullier, Evelyne; Tringali, Stephane; Devèze, Arnaud; Mom, Thierry; Darrouzet, Vincent; Truy, Eric
<x xml:space="preserve">Abstract</x> Objective To describe the reliability of the fully implantable middle ear transducer after successive technological changes. Study Design Prospective, observational, multicenter study. Setting Eight tertiary referral centers. Patients One hundred twenty-three adults were implanted with one of the five successive versions of the fully implantable middle ear implant between September 2005 and July 2012. Methods The reliability of each generation 2 years after implantation or at the maximal lifetime was reported by means of survival curves. Only technological failures were considered; non-technological failures were excluded from the analysis of reliability. Results One hundred fifty-seven devices were implanted during the period of study. Fifteen explantations were related to non-technological problems (e.g., infections, extrusions, etc.). One hundred forty-two implants were followed in the analysis of reliability. We observed 32 technical failures at 2 years. At the maximal lifetime of follow-up, 46 implants failed. The end of the follow-up was the first of November 2012. Survival rates at 2 years were 0%, 76.1%, 84.2%, 81.8%, and 100% for each of the successive available versions, respectively. Conclusion The reliability of the fully implantable middle ear implant improved over generations thanks to successive technological modifications that corrected the observed failures. The latest generation seems to be a reliable fully implantable middle ear implant system up to 22 months after implantation. The need to know the reliability of these active middle ear implants incites the creation of a follow-up register including patient's data and device failures to improve patient management.